Arbitrary Waveform Generation Based on Dispersion-Free Wavelength-to-Time Mapping Technique - Xinyi Zhu; Hao Sun; Wei Li; Ninghua Zhu; Ming Li (IEEE Photonics Journal, 2018)
We proposed and experimentally demonstrated an approach of dispersion-free arbitrary waveform generation based on a wavelength-swept laser, for the first time to the best of our knowledge. The system has been proven to generate a variety of waveforms, such as Gaussian pulses, rectangular pulses, and a chirped pulse with a large time-bandwidth product of 273.6. Thanks to the linear relationship of frequency to the time of the wavelength-swept laser, time-domain optical signal exhibits the user-defined shape of the optical spectrum without any dispersive element. Furthermore, the proposed method features simple structure, full reconfiguration, and, especially, the high potential for integration.